Abnormal Umbilical Artery Doppler Findings in the Recipient Twin Before Laser Surgery for Twin‐Twin Transfusion Syndrome. (1st May 2015) - Patel, Shivani; Quintero, Rubén A.; Kontopoulos, Eftichia V.; Korst, Lisa M.; Llanes, Arlyn; Chmait, Ramen H.
Abstract : Objectives: In twin‐twin transfusion syndrome (TTTS), persistent absent or reversed end‐diastolic flow in the umbilical artery is a rare finding in the recipient twin, and the clinical implications of this finding are not well characterized. We sought to study the clinical importance of abnormal umbilical artery Doppler waveforms in recipient twins and determine the perinatal survival of these twins after laser surgery. Methods: A retrospective study of patients with TTTS treated with laser surgery between 2006 and 2012 was conducted. Recipient twins with absent or reversed umbilical artery end‐diastolic flow on preoperative sonography were identified, and clinical and perinatal outcomes were compared to the remaining cohort. Statistical analyses were performed with Fisher exact and χ 2 tests. Results: Of 369 consecutive TTTS cases, 14 (3.8%) had absent or reversed umbilical artery end‐diastolic flow in the recipient twin. The rate of hydrops was higher in this group compared to those without absent or reversed flow (35.7% [5 of 14] versus 10.1% [36 of 355]; P = .0125). The rate of recipient twin growth restriction was also higher in the absent or reversed flow group (28.6% [4 of 14] versus 3.9% [14 of 355]; P = .0029). There was an increased rate of recipient fetal demise within 24 hours after surgery in those with absent or reversed flow (21.4% [3 of 14] versus 2.5% [9 of 355]; P = .0078), although there was no statistical difference in 30‐day survival between the groups (78.6% [11 of 14] versus 89.9% [319 of 355]; P = .1751). Conclusions: Doppler findings of absent or reversed umbilical artery end‐diastolic flow are rare in recipient twins. Although immediate post–laser surgery survival is relatively decreased in this group, overall perinatal survival rates appear to be favorable.